PGC-1β modulates catabolism and fiber atrophy in the fasting-response of specific skeletal muscle beds - Svenia Schmid; Barbara Heim-Kupr; Joaquín Pérez-Schindler; Shivani Mansingh; Markus Beer; Nitish Mittal; Nikolaus Ehrenfeuchter; Christoph Handschin (Molecular Metabolism, 2022)
Objective: Skeletal muscle is a pivotal organ for the coordination of systemic metabolism, constituting one of the largest storage site for glucose, lipids and amino acids. Tight temporal orchestration of protein breakdown in times of fasting has to be balanced with preservation of muscle mass and function. However, the molecular mechanisms that control the fasting response in muscle are poorly understood. Methods: We now have identified a role for the peroxisome proliferator-activated receptor γ coactivator 1β (PGC-1β) in the regulation of catabolic pathways in this context in muscle-specific loss-of-function mouse models. Results: Muscle-specific knockouts for PGC-1β experience mitigated muscle atrophy in fasting, linked to reduced expression of myostatin, atrogenes, activation of AMP-dependent protein kinase (AMPK) and other energy deprivation signaling pathways. At least in part, the muscle fasting response is modulated by a negative effect of PGC-1β on the nuclear factor of activated T-cells 1 (NFATC1). Conclusions: Collectively, these data highlight the complex regulation of muscle metabolism and reveal a new role for muscle PGC-1β in the control of proteostasis in fasting.